Divining a digital future mess and mythology in ubiquitous computing - Dourish, Paul (MIT Press, 2011)
Reflecting the interdisciplinary nature of the authors' collaboration, this book takes seriously the need to understand ubicomp not only technically but also culturally, socially politically and economically.